Evaluating the mandatory death penalty under section 398 of the dangerous drug act 1952 - Tan, P.; Lee, Y.H. (2007)
The mandatory death penalty under section 39B of the Dangerous Drugs Act 1951 is now 23 years old. This paper seeks to evaluate this penalty from two main perspectives: the nature of the death penalty itself, and the mandatory nature of the punishment under section 39B of the DDA. The first section traces the legislative history of section 39B and other provisions related to the offence of drug trafficking. The second section will examine, first, whether the mandatory death penalty has achieved the aims for which it was promulgated, and secondly, whether these aims are in fact-desirable, bearing in mind that the ultimate goal of any legal system is to achieve justice. The third section is an exposition on the international view of the death penalty. This paper will conclude with a summary of our findings.